RELATIONSHIP BETWEEN SECTIO CAESAREA AND NEONATORUM ASPHYSIA - Anggraini, Santi; Anggreni, Elsie; Susilo, Andrean; Bahriyah, Fitriyani (JURNAL IBU DAN ANAK, 2020)
ABSTRACT Background: The incidence of asphyxia neonatorum in developing countries ishigher than in developed countries.Method: The study design was analytic using across sectional approach. All data of maternal mothers in April-December 2017which were numbered 234 were analyzed using the chi-square formula.Results:From 82 mothers with primary caesarean section who had asphyxia were 27infants (33%). Of the 152 secondary cesarean delivery mothers there were 47infants with asphyxia (31%). The results of the chi-square analysis conducted,obtained a P-Value of 0.753.Conclusion: It can be concluded that there is norelationship between sectio caesarea from a midwife referral with the incidenceof asphyxia neonatorum in Indrasari Rengat District Hospital.